BNCC, educação infantil e as intervenções do mercado: alguns apontamentos - Amorim, Anna Thércia José Carvalho de (Universidade Federal do Tocantins, 2022)
This article aims to approach and analyze competences in early childhood education - learning rights - albeit in an incipient way and how they are described in the documents. The methodology used for this purpose was permeated by the qualitative approach supported by Bardin (1977) with a focus on bibliographic research and document analysis. The work is divided into four topics. In the first one, we present the documents that will be analyzed and the construction process of the National Curricular Common Base (BNCC). In the second topic, we highlighted the terms competences, skills, attitude and experience in the documents that support basic education, such as the National Curriculum Guidelines for Education and the BNCC. In the third moment, we problematize the intervention of the market in public education. In the fourth topic, we highlight the weaknesses of education caused by market interventions through public educational policies.